RPG GAME DESIGN FOR ENGLISH LEARNING - Tony Wibowo; Felnando Felnando (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Technology makes possible easier effort to study English language by social media, websites, books, or even seminars. RPG game is a type of game that tell the story and information by virtual and interactive path. In this study, we designed and developed an RPG game to help players learn English. The method that used to execute the study is ADDIE (Analysis, Design, Development, Implement, Evaluate) method. The result after development is the RPG game that can be used for players to learn English. After the game is implemented, the game can help student to learn English and playing at the same time.